HUBUNGAN STRES HIPERGLIKEMIA DENGAN INDEKS BARTHEL PASIEN STROKE HEMORAGIK AKUT DI BANGSAL SARAF RSUD ARIFIN ACHMAD PROVINSI RIAU - Danang Nugroho; Riki Sukiandra; Mukhyarjon " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTStress hyperglycemia is a condition of elevated blood glucose caused by disruption of the blood glucose regulation which is part of the non-specific reaction of stress or tissues damage. Stress hyperglycemia is common in acute diseases such as stroke, which significantly affect patient outcomes assessed with the Barthel Index. The purpose of this study is to find the correlation of stress hyperglycemia with Barhel index in patients with acute hemorrhagic stroke. Using observational analytic method with cross sectional design. The sample of this study are acute hemorrhagic stroke patients totaling 33 persons who confrom the inclusion criterias. Results of the study of 33 patients, found of stress hyperglycemia cases was 21 patients (63.6%) in acute hemorrhagic stroke. The discription of Barthel index in patients with acute hemorrhagic stroke are complete dependence (0-20) of 23 patients (69.69%), 10 patients (30, 30%) with severe dependence (21-61). There is positive correlation with moderate strength between stress hyperglycemia with Barthel Index in patients with acute hemorrhagic stroke (p = 0.001; r-0.513). The Conclusion is prevalence of stress hyperglycemia were 63.6% with the highest distribution of Barthel index is a full dependence totaling 23 patients (69.69%). There is positive correlation with moderate strength between stress hyperglycemia with Barthel Index in patients with acute hemorrhagic stroke (p = 0.001; r-0.513)Keywords: Stress hyperglycemia, Barthel Index, acute hemorrhagic stroke, ADL